A biosystematic analysis of Solanum acaule - Kardolus, J.P. (Wageningen University & Research, 1998)
This thesis describes a biosysternatic analysis of the allotetraploid species Solanum acaule . Solanum acaule is one of the circa 200 tuber-bearing Solanum species ( Solanum sect. Petota , Solanaceae) and often used in plant breeding programs for its disease resistances and frost tolerance. This species has the widest distribution of all wild potato species, from Ecuador into Argentina, and occurs at altitudes up to 4500 meter in the Andes. Together with the hexaplold S. albicans it forms the polyploid taxonomic series Acaulia . This study focuses on the hybrid speciation of series Acaulia . Solanum acaule shows morphological similarities with species of series Megristacroloba and Tuberosa , which have been hypothesized as possible ancestors. A phylogenetic study is conducted to unravel evolutionary relationships of Solanum acaule and its putative progenitors. Several morphological aspects of series Acaulia and related species are examined, and combined with a study of molecular markers. The thesis is completed with the proposal of a new subspecies of Solanum acaule. In a multivariate morphological analysis the boundaries of series Acaulia are determined and variation within the series is reconsidered. Inflorescence architectural traits, such as the dimensions of pedicels and corollas, are discussed in relation to the taxonomy of Solanum sect. Petota species, their habitat and breeding behavior. An unrecorded inflorescence type, which can be characterized as a monochasium with a strongly reduced peduncle and one or two 'extra' flowers in the axil of the subtending leaf, is described in series Acaulia. The taxonomy of Solanum sect. Petota often depends on quantitative characters. These are often variable, causing difficulties in species classification. However, series Acaulia is characterized by a qualitative character, i.e. a modified or even completely absent pedicel articulation. Normally, unfertilized flowers separate at the floral abscission zone which is located at this articulation. In an anatomical study this zone is proven to be absent in non- articulated pedicels of Solanum acaule. In S. albicans this zone is modified. These special features of pedicel articulation in series Acaulia are discussed in relation to the 'jointless'-mutations in tomato. The AFLP TMmolecular marker-technique is for the first time applied in Solanum taxonomy. Highly informative DNA fingerprints are produced with the AFLP-technique. Classifications based on AFLPs are generally in agreement with current taxonomic opinions, but also new evolutionary insights are revealed. The results of the present AFLP study casts doubt on the status of certain taxonomic series, and the classification of particular species into these series. Based on the neighbor-joining analysis of the AFLP data it is concluded that the hexaploid Solanum demissum (from Mexico) is likely to be closely related to both the South American series Acaulia and the Central American polyploid series Longipedicellata, and feasibly a hybrid descendant of these series. Series Acaulia itself is a monophyletic group in the cladistic analyses, and it is most advanced in the cladograms. In addition to the AFLP study, an isozyme analysis has been conducted on series Acaulia and its closest relatives. Based on both AFLP and isozyme data, it is concluded that series Acaulia is indeed most closely related to series Tuberosa and Megistacroloba. However, it is not a simple derivative of a hybridization event of species of these two series, but more probably one of its ancestors could have belonged to the series Megistacroloba / T uberosa affiliation. The second ancestor that provided the unique characters to series Acaulia is still unknown, and possibly extinct.